OPTIMALISASI PENGGUNAAN ALAT BANTU PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SERVIS ATAS - Sunardi Sunardi (PHEDHERAL, 2018)
The aim of the research is to improve the service learning outcomes of the volleyball through aids such as hula hoop, javelin, raffia cord, net, cone, plastic ball, sponsors ball in the learning process of students of SMA N 4 Surakarta.            This research is a classroom action research (CAR). This research was conducted in two cycles which each cycle consists of planning, implementation of the action, observation, reflection. The subjects of the research are the students of class X IIS 4 SMA N 4 Surakarta academic year 2016/2017, with the number of 30 students, 13 students and 17 students. Sources of data in this study are primary data and secondary data. Technique of collecting data with test and observation. Data validity using method triangulation. Data analysis using percentage technique, where from the data that has been obtained, then analyzed by percentage to see the learning result in volleyball game on learning in school.         The results showed that learning with the optimization of the use of tools can improve the learning outcomes of service on volleyball in students of class X IIS 4 SMA N 4 Surakarta 2016/2017 academic year. In the first cycle, the results of service learning on the volleyball students reached 63.33% or 19 students of 30 students have entered the criteria thoroughly while 11 students or 36.67% in the category has not been completed. In the second cycle there is an increase in the percentage of student learning outcomes in the category of completion of 83.33% or a number of 25 students. Until the end of the meeting there are 5 students or 16.67% that have not been completed.Based on the result of the research, it can be concluded that the learning with the optimization of the use of the tools can improve the learning outcomes of service on the volleyball in the students of class X IIS 4 SMA N 4 Surakarta in the academic year 2016/2017.